Gynecologic oncology patients are ready for telemedicine in routine care: Results from a pre-COVID survey - J. Dholakia; J. Kim; M.I. Liang; R.C. Arend; K.S. Bevis; J.M. Straughn, Jr; C.A. Leath, III; W.K. Huh; H.J. Smith (Elsevier, 2021)
Objectives: To assess telemedicine readiness of gynecologic oncology patients, particularly those at risk for care access disparities (increased distance to care, rural populations.) Methods: Patients at all disease/treatment stages completed an anonymous survey during in-person outpatient appointments at an academic comprehensive cancer center from 1/6/2020 to 2/28/2020, conducted prior to the COVID-19 pandemic, before the introduction of telemedicine in this practice. Results: Of 180 patients approached, 170 completed the survey (94.4%). Mean age was 59.6 years; 73.4% identified as White, 23.7% Black, and 2.9% other race. Ovarian cancer was most common (41.2%), followed by endometrial (27.1%), cervical (20.6%), and vaginal/vulvar (7.1%). Most patients traveled > 50 miles for appointments (63.8%); they were more likely from rural counties with significantly higher travel costs/visit ($60.77 vs $37.98, p = 0.026.) The majority expressed interest in using telemedicine (75.7%) or a smartphone app (87.5%) in their care. The majority of patients with difficulty attending appointments (88.9 vs 70.2%, p = 0.02) or from rural counties (88.7% vs 69.6%, p = 0.03) were interested in telemedicine; those with both characteristics reported 100% interest. The majority in both urban and rural counties had home internet access, and reported similarly high rates of daily use (79% vs 75%). Race and age were not associated with differences in internet access or use or telemedicine interest. Conclusions: Telemedicine is attractive to the majority of patients and may offer financial/logistical advantages. Patients have high internet use rates and comfort with using technology for healthcare. Telemedicine should be incorporated into standard practice beyond the COVID-19 pandemic to reduce healthcare access disparities.